OVERVIEW OF TOILET TRAINING IN TOODLER - Indari Indari; Hanim Mufarokhah; Siti Maisaroh; Tien Aminah (Program Studi Keperawatan, Fakultas Ilmu Kesehatan, ITSK RS dr Soepraoen, 2024)
One of the problems of parents who have toddler are toilet training children is that they don't understand their children's readiness, some parents are busy with work or are lazy about taking their children to the toilet. The failure of children aged 2-3 years who use diapers is a lack of parental, psychological and mental readiness. The aim of the research is to determine the toilet training in toodler who use diapers. This research is quantitative research with a descriptive research design. The population in this study were all toodler who used diapers in Distric of Kedungkandang Malang City, a total of 55 children. Sampling uses purposive sampling. This research was conducted on 04 - 10 June 2022. The research instrument used was univariate or frequency distribution. The research results showed that the majority of respondents were unsuccessful, namely 60%, and a small number of respondents were successful 40%. These results illustrate that the success of toilet training in children aged 2-3 years who use diapers is mostly unsuccessful. Based on the research results, it is hoped that we will continue to provide education and learning about toilet training for success, which requires maternal readiness, physical readiness and psychological readiness.